Macys, Inc. : redrafting the brand architecture - Lamb, Amanda M., (SAGE Knowledge. Cases., 2017)
Macys controversial conversion of Chicago's State Street Marshall Fields store is just one of many branding and customer loyalty challenges facing Macys Inc. today. After converting over 800 stores nationwide, Macys focus is to remain relevant and competitive by managing customer perception of quality as well as reinvigorating the department store experience.